'Subaltern' pushbacks: An analysis of responses by Facebook users to 'racist' statements by two French doctors on testing a COVID-19 vaccine in Africa. (1st September 2021) - Mudavanhu, Selina Linda
In April 2020, two French doctors discussed on television the idea of testing a COVID-19 vaccine in Africa. The controversial utterances were widely condemned, subsequently leading the doctors apologizing. Using thematic analysis, and drawing on Stuart Hall's encoding‐decoding model and the concepts of coloniality and decoloniality, this article analyses responses to the doctors' statements by social media users. Of the decoding positions proposed by Stuart Hall, many Facebook users occupied the oppositional decoding position. Facebook users dethroned ideas rooted in colonialism that positioned Europeans as superior thought leaders and Africans as inferior and passive recipients of western knowledges and leadership. They also dismissed the doctors as flagrant racists. Facebook users affirmed that Africans were not guinea pigs and Africa was not a laboratory. The visceral pushbacks by social media users discredited and delegitimized the doctors' ideas as well as to foster solidarity among Africans in disparate locations.